Modelling an electrochemically roughened porous platinum electrode for water oxidation. Issue 21 (22nd February 2016) - Weremfo, Alexander; Lu, Xunyu; Carter, Paul; Hibbert, D. Brynn; Zhao, Chuan
Abstract : The use of a central composite design to model the roughness of an electrochemically roughened Pt electrode and the surface with a well-defined nanostructure exhibits greatly improved catalytic activity towards oxygen evolution reaction. Abstract : Pt is usually not considered as an efficient catalyst for water oxidation. Here, we report a design-of-experiment approach for modelling the roughness of an electrochemically roughened Pt electrode for water oxidation. The results indicate significant interaction between oxidation and reduction potentials on surface roughness and the porous Pt exhibits greatly improved catalytic activity for oxygen evolution in acid which is comparable to the benchmark catalyst RuO2 .